2022
DOI: 10.1007/978-3-030-93907-6_71
|View full text |Cite
|
Sign up to set email alerts
|

Ontological Modeling of Electronic Educational Resources

Abstract: The organization of educational information through innovative computing technology allows to move away from the linear organization of the learning space, thereby creating its "volumetric" analogue. In the modern view one of the effective means for the structural and logical construction of electronic educational resources as rather complex knowledge systems is ontology.Ontology is an attempt at a comprehensive and detailed formalization of a field of knowledge using a conceptual schema which usually consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Під інформаційно-освітнім середовищем розуміємо сукупність природних і штучно створених чинників, які впливають на освітній процес закладу чи установи освіти. Або, дещо ширше, освітнє середовище освітньої установи -це загальний, сукупний, об'єднаний, інтегральний, цілісний фактор розвитку особистості, що грає визначальну роль у модифікації поведінки, яка розгортається як внаслідок запланованих, так і незапланованих факторів середовища, сприяє особистісному та професійного розвитку 9 .…”
Section: рис 1 інформаційне середовище в інформаційному просторіunclassified
“…Під інформаційно-освітнім середовищем розуміємо сукупність природних і штучно створених чинників, які впливають на освітній процес закладу чи установи освіти. Або, дещо ширше, освітнє середовище освітньої установи -це загальний, сукупний, об'єднаний, інтегральний, цілісний фактор розвитку особистості, що грає визначальну роль у модифікації поведінки, яка розгортається як внаслідок запланованих, так і незапланованих факторів середовища, сприяє особистісному та професійного розвитку 9 .…”
Section: рис 1 інформаційне середовище в інформаційному просторіunclassified
“…In [4] it is shown that the use of semantic technologies for EC modeling is one of the examples of the use of the ontological approach. The authors show that the potential of ontological modeling is determined by the features of using EC in the educational process.…”
Section: Introductionmentioning
confidence: 99%
“…-underutilization of the computer ontologies potential (as a method of creating ordered structures) in the educational process [4];…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, it was found that existing electronic educational resources do not fully cover curricula, in many ways they are outmoded (their modernization has not kept pace with the dynamics of the needs of the educational process), etc. In addition, many electronic textbooks and manuals are of dubious quality due to the use of outdated or unapproved terminology, the lack of methods for developing resources of this type, and a number of other reasons [1].…”
mentioning
confidence: 99%